Research of consumers' attitude to university commercials by using neuromarketing approach - Smykova, M.R.; Orazgaliyeva, E.B.; Kazybaeva, A.M.; Abuzhalitova, A.A. (BUKETOV BUSINESS REVIEW, 2021)
Object: The article presents and reveals the features of neuromarketing and the possibilities of application in applied research. Based on the conducted neuromarketing research of university commercials, the emotional reaction of consumers has been determined, which affects memorability and relation to commercials. Methods: Desk research of theoretical material based on secondary information, neuromarketing research using the FaceReader device to identify micro facial expressions of respondents. Results: Theoretical analysis showed the possibility of using neuromarketing in evaluating commercials, as well as a model of emotional response to advertising. Neuromarketing researches have made it possible to summarize the results and understand the structure of emotional perception of three universities commercials. Conclusions: On the basis of the results of neuromarketing researches, it can be concluded that some respondents have cognitive dissonance, i. e. the consumer experiences conflicting feelings. The analysis of the respondents' facial expressions allows to determine the rating of different feelings when viewing university commercials and form an emotional connection with the brand. Thus, enterprises will be able to adjust their marketing and economic strategies to take advantage of the competitive positioning of their brands